2020
DOI: 10.1111/ajt.16133
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged SARS-CoV-2 shedding and mild course of COVID-19 in a patient after recent heart transplantation

Abstract: In the coronavirus disease 2019 (COVID‐19) pandemic, organ transplant recipients are considered to be at high risk for an unfavorable outcome. However, in particular the role of immunosuppression in patients infected with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) remains undetermined. Here, we present a 62‐year‐old male COVID‐19 patient with recent heart transplantation who developed only mild symptoms, but had prolonged virus shedding, and summarize the available data on COVID‐19 in cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 24 publications
3
91
0
3
Order By: Relevance
“…Patients with albumin ≥ 35 g/L had a shorter duration of viral RNA shedding compared with those with albumin < 35 g/L, and the median times were 18 days and 20 days, respectively. Campioli et al and Decker et al suggested that the immunosuppressive therapy may contribute to delayed clearance of virus [11,14]. In addition, Campioli et al suggested that asthma may be a cause of delayed recovery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with albumin ≥ 35 g/L had a shorter duration of viral RNA shedding compared with those with albumin < 35 g/L, and the median times were 18 days and 20 days, respectively. Campioli et al and Decker et al suggested that the immunosuppressive therapy may contribute to delayed clearance of virus [11,14]. In addition, Campioli et al suggested that asthma may be a cause of delayed recovery.…”
Section: Resultsmentioning
confidence: 99%
“…In our review, immunosuppressive therapy was identified as a possible contributing factor for delayed clearance of the virus [11,14]. Similarly, Zhu et al reported prolonged detection of viral RNA in immunosuppressed renal transplant patients [34].…”
Section: Tearsmentioning
confidence: 90%
See 1 more Smart Citation
“…Though to date, relatively few immunocompromised patients have died of COVID-19 relative to the general population, prolonged illness and prolonged viral shedding has also been described, which could increase risk for other patients and staff. 37,38 Furthermore, even after recovery, this population is likely to be at risk for re-infection due to compromised adaptive responses. Adoptive T-cell immunotherapy may accordingly be beneficial for prevention or early treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…27 Both of the case reports which identified SARS-CoV-2 in culture beyond day 14 were of hospitalised patients with mild disease, 25 , 30 case reports described an immunocompromised patient who had recently had a heart transplantation. 25…”
Section: Virus Culture Study Findingsmentioning
confidence: 99%